Wastewater management in A Nigerian leper colony - Coker, Akinwale O.; Oluremi, Johnson R.; Adeshiyan, Rebecca A.; Sridhar, Mynepalli K.; Coker, Morenike E.; Booth, Colin A.; Millington, Jennifer A.; Khatib, Jamal M. (Journal of Environmental Engineering and Landscape Management, 2011)
Wastewater from infected leprosy patients is expected to contain considerably higher concentrations of pathogens than standard domestic wastewater and, therefore, is more infectious. Isolation of lepers' is thought to prevent the spread of a wide range of infectious diseases that could potentially be contacted through direct or indirect exposure from an infected person's wastewater in the surrounding environment. However, inappropriate management of wastewater and sewage from these camps has led to contamination of the surrounding environment, typical in Nigeria. This study aims to recommend safe, efficient and sustainable management of wastewater and sewage in a lepers' colony in Ogbomosho, south west Nigeria. The case study is privately owned, with three camps and a leprosarium. Information and data (primary and secondary) were collected from medical personnel (doctors, matrons and nurses), management staff and lepers in each camp, through handdelivered and orally explained questionnaires and physical observations. Wastewater samples could not be collected for analysis because there were no septic tanks or drainage for sewage and wastewater disposal. Two of the camps have no sanitary disposal system, with the remaining camp occupying one pit latrine, which is inadequate in prevention of environmental pollution. The leprosarium itself uses the pit latrine as an improvised bathroom and for defecation. Therefore, a further aim of this work is to provide a sewage treatment facility to cope with the problem of unsanitary disposal of excreta. The majority of wastewater is generated from bathing, personal washing, ward clean-ups, patients' services and general house-keeping activities. The approximate quantity of water being used per head per day was found to be 64-79 litres, resulting in 60 litres of wastewater that was discharged without treatment. To ameliorate environmental risks that leper colonies are responsible for, the pour-flush toilet was recommended based on its suitability for the physical condition of lepers, its ease of operation, maintenance and sustainability, minimum water usage for flushing and low construction costs. However, this must be fed into a well designed and sited septic tank and soak-away pit to receive foul sewage and sullage, respectively. Ideally, construction of a proper in-built bathroom is recommended for both the leprosarium and camps.Article in English.Raupsais užsikrėtusių žmonių kolonijos nuotekų tvarkymas Nigerijoje Santrauka. Manoma, kad raupsais užsikrėtusių pacientų naudoto vandens nuotekose gali būti padidėjusi patogeninių organizmų koncentracija, palyginti su nuotekomis iš gyvenamųjų namų. Manyta, kad raupsuotųjų izoliavimas sulaikys šios infekcinės ligos plitimą didesniu mastu, nes mažiau infekuotųjų nuotekų pateks į aplinką. Vis dėlto netinkamas nuotekų tvarkymas Nigerijoje lėmė stovyklas supančios aplinkos užteršimą. Darbo tikslas–pateikti rekomendacijų, kaip saugiau, efektyviau ir tvariau sutvarkyti nuotekų valymo sistemą Ogbomosho kolonijoje pietvakarių Nigerijoje. Teikiant rekomendacijas remtasi trijų privačioje teritorijoje esančių stovyklų ir leprozoriumo pavyzdžiu. Kiekvienoje stovykloje informacija ir duomenys (pirminiai ir antriniai) buvo surinkti iš medicinos sektoriaus personalo (gydytojų, seselių), administracijos ir raupsais užsikrėtusių žmonių užpildytų anketų ar apklausus žodžiu bei apžiūrėjus fiziškai. Nuotekų mėginiai negalėjo būti paimti, nes nebuvo surinkimo tankų ar nuotekų kanalizacijos sistemos. Dvi stovyklos neturi sanitarinės šalinimo sistemos, trečioji stovykla turi vieną iškastą duobę. Tai visiškai neatitinka aplinkosauginių reikalavimų. Pačiame leprozoriume iškastos duobės naudojamos kaip improvizuoti vonios kambariai ir tualetai. Tolesnis šio darbo tikslas–numatyti valymo įrenginius, kurie padėtų įveikti šias problemas. Didėlė dalis nuotekų susidaro maudymosi, skalbimo, palatų valymo, pacientų aptarnavimo ir buities darbų metu. Apytiksliai venas žmogus per dieną sunaudoja 64–79 litrus vandens, gi nesutvarkytų nuotekų išleidžiama apie 60 litrų per dieną. Dėl raupsais užsikrėtusių žmonių kylančiam pavojui aplinkai sumažinti rekomenduota naudoti vandens nuleidimo sistemą tualetuose. Vandens nuleidimo sistemos įdiegimas yra tvarus sprendimas, nes nėra brangus, o pasiekiama, kad vandens būtų sunaudojama minimaliai. Be to, nutekamasis vanduo turi būti surenkamas tam skirtuose tankuose ir duobėse. Idealiu atveju–ir leprozoriume, ir stovyklose rekomenduotina įrengti tinkamus vonios kambarius.Reikšminiai žodžiai: nuotekos, tvarkymas, aplinka, politika, infekcija, sanitarinė įranga, tvarumas.Приведение в порядок системы стоков в колонии зараженных проказой людей в НигерииРезюме. Считается, что в сточных водах из колоний зараженных проказой людей может быть увеличена концентрация патогенных организмов по сравнению со сточными водами из жилых домов. Ранее предполагалось, что изоляция зараженных проказой людей предотвратит распространение этой инфекционной болезни в большом масштабе благодаря уменьшению возможности попадания в окружающую среду инфицированных сточных вод. Однако изза характерной для Нигерии плохой очистки сточных вод окружающая колонию среда оказалась загрязненной. В работе приводятся рекомендации, как безопаснее и эффективнее оборудовать систему очистки сточных вод в колонии Огбомошо на юго-западе Нигерии. Рекомендации приводятся на примере трех лагерей и лепрозория, находящихся на частной территории. Информация и другие данные (первичные и вторичные) в каждом лагере были получены у медицинского персонала (врачей, старших сестер и др.), администрации и зараженных проказой людей, которые опрашивались устно, осматривались физически или заполняли розданные им анкеты опроса. Образцы сточных вод не забирались, так как не существовало танков для сбора стоков или канализационной системы. В двух лагерях не было санитарной системы для удаления стоков, в третьей была выкопана одна яма, что совершенно не удовлетворяет природоохранных требований. В самом лепрозории выкопанные ямы использовались как импровизированные ванные комнаты и туалеты. Поэтому целью работы было способствовать внедрению очистных сооружений, которые могли бы решить существующую антисанитарную проблему. Большую часть сточных вод составляет вода, загрязненная во время купания, стирки, уборки палат, обслуживания пациентов и бытовых работ. Один человек за день использует приблизительно 64–79 литров воды, в то время как за день спускается около 60 литров неочищенных отходов. Для того, чтобы снизить опасность для окружающей среды от прокаженных людей, было рекомендовано использовать систему спуска воды в туалетах в зависимости от физического состояния зараженных проказой людей, что улучшило бы возможности использования воды и приведения в порядок системы стока. Внедрение системы спуска воды является наиболее приемлемым решением, так как не требует больших материальных затрат и ограничивается минимальным количеством используемой воды. Сточная вода должна собираться в предназначенных для этого танках и ямах. В идеальном случае оборудование соответствующих ванных комнат рекомендовано как для лепрозория, так и для лагерей.Ключевые слова: стоки, приведение в порядок, окружающая среда, политика, инфекция, санитарное оборудование.